Transition phase towards psoriatic arthritis: clinical and ultrasonographic characterisation of psoriatic arthralgia. Issue 2 (23rd October 2019) - Zabotti, Alen; McGonagle, Dennis G; Giovannini, Ivan; Errichetti, Enzo; Zuliani, Francesca; Zanetti, Anna; Tinazzi, Ilaria; De Lucia, Orazio; Batticciotto, Alberto; Idolazzi, Luca; Sakellariou, Garifallia; Zandonella Callegher, Sara; et al.
Abstract : Objective: Non-specific musculoskeletal pain is common in subjects destined to develop psoriatic arthritis (PsA). We evaluated psoriatic patients with arthralgia (PsOAr) compared with psoriasis alone (PsO) and healthy controls (HCs) using ultrasonography (US) to investigate the anatomical basis for joint symptoms in PsOAr and the link between these imaging findings and subsequent PsA transition. Methods: A cross-sectional prevalence analysis of clinical and US abnormalities (including inflammatory and structural lesions) in PsOAr (n=61), PsO (n=57) and HCs (n=57) was performed, with subsequent prospective follow-up for PsA development. Results: Tenosynovitis was the only significant sonographic feature that differed between PsOAr and PsO (29.5% vs 5.3%, p<0.001), although synovitis and enthesitis were numerically more frequent in PsOAr. Five patients in PsOAr and one in PsO group developed PsA, with an incidence rate of 109.2/1000 person-years in PsOAr vs 13.4/1000 person-years in PsO (p=0.03). Visual Analogue Scale pain, Health Assessment Questionnaire, joint tenderness and US active enthesitis were baseline variables associated with PsA development. Conclusion: Tenosynovitis was associated with arthralgia in subjects with psoriasis. Baseline US evidence of enthesitis was associated with clinical PsA development in the longitudinal analysis. These findings are relevant for enriching for subjects at risk of imminent PsA development.